Core Ethical Values of Character Education Based on Islamic Values in Islamic Boarding Schools - Ihin Solihin; Aan Hasanah; Hisny Fajrussalam (International Journal on Advanced Science, Education, and Religion, 2020)
This research was motivated by the spread of radicalism ideology that’s carried out by leaders of some boarding schools (Islamic school of Qur’anic studies), the degradation of society moral, and the immoral behavior in education institutions. This research aims to investigate the core ethical values of character education based on Islamic values in Islamic boarding schools to facilitate the embedding of those values in Indonesian society so that the radicalism ideology, moral degradation, and immoral behavior can be eliminated. This research uses a qualitative approach and method. The type of research is library research; data were obtained from books, journals, and other relevant references. Then the data were analyzed by using content analysis techniques. The result of this research shows that the core ethical values of character education based on Islamic values in Islamic boarding schools are divided into four core teachings of Islamic studies, namely al-fiqh (fiqh), al-tauhid (monotheism), al-tasawuf (Sufism), and al-akhlaq (moral). Values consist in those four core teachings are cleanliness, health, neatness, faith, piety, belief toward blessing (baraka), moderate, benignity, simplicity, self-attitude of accepting and feeling sufficient for the results of his efforts (qonaah), sincerity, humility, religious culture, respect for older people, and hard work. Keywords: Education Character, Islamic Values, Ethical Value